Manajemen Program Tiga Bahasa di Pondok Pesantren Salafiyah Daarul Huda Sukoharjo - Puput Mulyono; Nur Hadi (STIKes Ibnu Sina Ajibarang, 2024)
The impetus driving this investigation is fundamentally that a trilingual curriculum is essential to prepare students for global competitiveness due to their mastery of English. and Arabic. This research aims to explore the execution, evaluation, and find out the difficulties and obstacles in the trilingual program based on holistic education at Daarul Huda Islamic Boarding School Sukoharjo. This research method is descriptive qualitative. This study employs various data gathering methods including interviews, observations, documentation, and surveys. The technique for analyzing data entails three phases: data reduction, data representation, and conclusion drawing. The findings of this research reveal that the execution of the trilingual program manifests as the use of English in English classes. The assessment of the bilingual program, based on a holistic educational approach, incorporates practice, training, and enrichment activities. Challenges and hurdles faced include students’ incomplete comprehension of the learning process conducted in English. This research concludes that the execution of a holistic education-oriented bilingual program is achieved through the application of three distinct curricula featuring diverse methodologies, the recruitment of educators proficient in English, and the incorporation of mixed languages during instruction. Teacher evaluations are performed through monthly meetings organized by school administration, while student evaluations occur through daily assignment reviews, mid-term exams, and final examinations. The challenges encountered include varying student capabilities, diverse family support levels, and some students’ lack of understanding regarding the advantages of language education.